The Effect of Earning Per Share, Net Profit Margin, and Operating Cash Flow on Stock Prices in Food and Beverage Sector Companies Listed on the IDX for the 2018-2022 Period - Tilawatil Ciseta Yoda; Martina Lifati Lofa; Tafdil Husni; Elvira Luthan; Rida Rahim (Adpebi Science Series, 2024)
This study aims to test the Effect of Earning Per Share, Net Profit Margin, and Operating Cash Flow onStock Price. Based on the results of the hypothesis testing conducted in this study, it can be concluded that partiallyEarning Per Share has a significant positive effect on the Stock Price with a calculated value of 7.713 > t table 1.703 anda significant amount of 0.00 < 0.05 so that the H1 hypothesis can be accepted. Ner Profit Margin has a significantpositive effect on the Stock Price with a t-value of 5.284 > t table 1.703 and a significant amount of 0.000 < 0.05 so thatthe H2 hypothesis can be accepted. The size of the company has a positive effect on the Stock Price where the valueof t is calculated at 1.801 > t table 1.703 and is significant at 0.076 > 0.05 so that the H3 hypothesis is rejected. Earning PerShare, Net Profit Margin, and Operating Cash Flow to the stock price with a value of f calculated 52.325 > f table 2.98 andsignificant 0.000 < 0.05 so that the H4 hypothesis can be accepted. So it can be concluded that Earning Per Share(X1), Net Profit Margin (X2), and Operating Cash Flow (X3) to the Stock Price (Y) obtained the value of thedetermination coefficient written R Square of 0.707, it can be explained that the proportion of Earning Per Share, NetProfit Margin, and Operating Cash Flow to the Stock Price is 70.7% while the remaining 29.3% is influenced by otherfactors other than the variables used in this study.